Economic policy uncertainty and investment in Spain - Daniel Dejuan-Bitria; Corinna Ghirelli (SERIEs - Journal of the Spanish Economic Association, 2021)
The aim of this paper is to investigate the effect of economic policy uncertainty on firms' investment decisions. We focus on Spain for the period 1998-2014. To measure policy-related uncertainty, we borrow the economic policy uncertainty (EPU) indicator available for this country. We find strong evidence that uncertainty reduces corporate investment. This relationship appears to be nonlinear, being the marginal effect of uncertainty attenuated toward zero during periods of high uncertainty levels. Furthermore, the heterogeneous results suggest that the adverse effect of uncertainty is particularly relevant for highly vulnerable firms. Overall, these results are consistent with the hypotheses that economic policy-related uncertainty reduces corporate investment through increases in precautionary savings or to worsening of credit conditions.
Keywords: D80; E22; G18; G31; G38; 330; Corporate investment; Economic policy uncertainty; EPU; Financial frictions